Hak Tolak Seorang Ahli Waris Dalam Perspektif Kitab Undang-Undang Hukum Perdata Dan Hukum Islam - EMILDA KUSPRANINGRUM (Jurnal Risalah Hukum, 2008)
The inheritance process refers to a natural process in following after the death leavinga wealth, either asset or liability, to the beneficiary. But two different laws of inheritanceremain in the Indonesia due to the different views on it. The most prominent relates to theRights of Rejection by the beneficiary. Indonesian positive law admits the rights of rejectionby the beneficiary, but Islamic Law underlines the responsibility of the beneficiary toward theheir considering the matter of mundane and divinity.Key words: hak tolak (rejection rights), waris (inheritance), pewaris (heir), ahli waris (beneficiary).